1995
DOI: 10.3758/bf03198931
|View full text |Cite
|
Sign up to set email alerts
|

Trial spacing effects in pavlovian conditioning: A role for local context

Abstract: Two conditioned lick-suppression experiments with rats were conducted in order to replicate and extend findings by Ewing, Larew, and Wagner (1985). Ewing et al. observed that excitatory responding to a CS paired with a footshock US was attenuated when the ITIs that preceded each CS-US trial were short (60 sec) relative to when they were long (600 sec). This effect was isolated in the influence of the preceding ITI because the preceding ITI was consistently short for one CS and consistently long for a different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
2
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 16 publications
(23 reference statements)
1
28
2
3
Order By: Relevance
“…Indeed, it is likely that the function, when properly evaluated, has the form of an inverted U and this seems to be the case for both contexts and cues. Thus, there is nothing special about context in terms of spatial learning and exposure/responding functions, rather these results seem to be found under extreme parametric variations that, when properly assessed, show that both context and cues display similar functions (Barnet, Grahame, & Miller, 1993a; 1993b; 1995). …”
Section: Some Misconceptions About Contexts and Environmentsmentioning
confidence: 94%
“…Indeed, it is likely that the function, when properly evaluated, has the form of an inverted U and this seems to be the case for both contexts and cues. Thus, there is nothing special about context in terms of spatial learning and exposure/responding functions, rather these results seem to be found under extreme parametric variations that, when properly assessed, show that both context and cues display similar functions (Barnet, Grahame, & Miller, 1993a; 1993b; 1995). …”
Section: Some Misconceptions About Contexts and Environmentsmentioning
confidence: 94%
“…There was no significant size ‫ן‬ stimulus interaction (F < 1) nor was there an effect of stimulus pair (F (3,28) = 1.00, P = 0.41.) Experiment 3: Optimizing inter-trial interval, trials per session, and trial initiation requirements Behavioral experiments have shown that learning proceeds more rapidly when inter-trial intervals (ITIs) are long than when they are short (e.g., Barnet et al 1995). Therefore, in Experiment 3, we compared the rate of learning with two different ITIs, 5 sec (the ITI used in most previous touchscreen experiments) and a longer 20 sec.…”
Section: Experiments 2: Optimizing Stimulus Sizementioning
confidence: 99%
“…(2) Animals may also learn additional stimuli; contextual parameters may be particularly influential. Barnet et al (1995), in conditioning rats to light or tone with an aversive stimulus, have argued that local contextual stimuli may be more influential for shorter ITI than for longer ITI in modulating conditioned response. Conversely, exposing the animals to the context for longer times during spaced conditioning may favor retention.…”
Section: Massed and Spaced Learningmentioning
confidence: 99%